Question
upstudy study bank question image url

All the real zeros of the given polynomial are integers. Find the zeros. (Enter your answers as a comma-separated list. Enter all answers using the appropriate multiplicities.) \[ P(x)=x^{3}+4 x^{2}-3 x-18 \] Write the polynomial in factored form. \( P(x)=\square \)

Ask by Barnett Ellis. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Zeros: 2, -3, -3 Factored Form: \( P(x) = (x - 2)(x + 3)^2 \)

Solution

To find the zeros of the polynomial P(x) = x³ + 4x² - 3x - 18, we begin by testing possible integer roots using the Rational Root Theorem. 1. Test x = 2:   P(2) = 2³ + 4(2²) - 3(2) - 18 = 8 + 16 - 6 - 18 = 0   Thus, x = 2 is a zero. 2. Divide P(x) by (x - 2) to factor the polynomial:   Using synthetic division with root 2:     Coefficients: 1, 4, -3, -18     Bring down 1:     Multiply 1 × 2 = 2; add to 4 gives 6.     Multiply 6 × 2 = 12; add to -3 gives 9.     Multiply 9 × 2 = 18; add to -18 gives 0.   The quotient is x² + 6x + 9. 3. Factor the quadratic x² + 6x + 9:   x² + 6x + 9 = (x + 3)² Thus, the factored form of the polynomial is:   P(x) = (x - 2)(x + 3)² The zeros of the polynomial are:   x = 2 and x = -3 (with multiplicity 2). Final Answer:   Zeros: 2, -3, -3   Factored Form: P(x) = (x - 2)(x + 3)²

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To find the real zeros of the polynomial \( P(x) = x^3 + 4x^2 - 3x - 18 \), we can use the Rational Root Theorem, which suggests that possible rational zeros are the factors of the constant term (-18) divided by the factors of the leading coefficient (1). The possible rational roots are ±1, ±2, ±3, ±6, ±9, ±18. By testing these potential zeros, we find that \( x = 2 \) is a root since \( P(2) = 2^3 + 4(2)^2 - 3(2) - 18 = 8 + 16 - 6 - 18 = 0 \). We can then use synthetic division to factor the polynomial \( P(x) \) by \( (x - 2) \). After performing synthetic division, we get: \[ P(x) = (x - 2)(x^2 + 6x + 9) \] The quadratic \( x^2 + 6x + 9 \) can be factored further: \[ x^2 + 6x + 9 = (x + 3)^2 \] Thus, we can express \( P(x) \) as: \[ P(x) = (x - 2)(x + 3)^2 \] The real zeros of the polynomial are 2 and -3 (with multiplicity 2). Therefore, the final answers are: Zeros: \( 2, -3, -3 \) Factored form: \[ P(x) = (x - 2)(x + 3)^2 \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy